2007
DOI: 10.1007/s11552-007-9054-2
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Boxer's Fractures Treated by a Soft Wrap and Buddy Taping: A Prospective Study

Abstract: Introduction The ideal treatment for a boxer's fracture remains controversial, particularly the degree of volar dislocation considered acceptable for nonoperative treatment. Patients and Methods From December 2003 to December 2004, 25 patients who sustained a subcapital metacarpal fracture of the little finger with volar angulation between 30 to 75°were prospectively enrolled in the study. All patients were treated with a circular self-adherent wrap covering metacarpal bones II-V and buddy taping of the ring a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 31 publications
1
23
0
1
Order By: Relevance
“…13,14 The proposed limit of fracture angulation to minimize functional deficit is 30°, without shortening or rotational deformity. 15 However, prospective, randomized studies have shown that regardless of fracture angulation or treatment method, adequate short-term [16][17][18][19][20] and long-term 21 outcomes are achieved. The current comprehensive systematic review of all available prospective, randomized studies compares reduction and splint immobilization vs soft wrap without reduction of boxer's fractures.…”
mentioning
confidence: 99%
“…13,14 The proposed limit of fracture angulation to minimize functional deficit is 30°, without shortening or rotational deformity. 15 However, prospective, randomized studies have shown that regardless of fracture angulation or treatment method, adequate short-term [16][17][18][19][20] and long-term 21 outcomes are achieved. The current comprehensive systematic review of all available prospective, randomized studies compares reduction and splint immobilization vs soft wrap without reduction of boxer's fractures.…”
mentioning
confidence: 99%
“…The healthy digit acts as a splint, keeping the damaged one in a natural position for healing. It is a well known useful method for treating sprains, dislocations, and other injuries of fingers or toes, especially fifth metacarpal fractures 1,2). Some comparative studies of casting versus taping to treat fifth metacarpal fractures reported that taped patients recovered more quickly and with superior functionality than those in the cast group 1)…”
mentioning
confidence: 99%
“…The economic burden is particularly high in these patients as they typically affect young and healthy men (7) leading to missed time from work. Isolated metacarpal injuries can result in up to 3 - 6 weeks of missed time with non-operative management alone (8-10). Therefore, optimizing treatment of these injuries may have significant benefits in both quality of life and return to work for these patients.…”
Section: Contextmentioning
confidence: 99%